Optimization of Hospital Health Services: Insights from Recent Literature - Parindra, I Ketut; Menap, Menap; Khalik, Lalu Abdul (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The objective of this study is to conduct a comprehensive literature review to identify and analyze strategies for optimizing hospital health services within the last year. Utilizing the PRISMA methodology, the study systematically reviewed articles from the SCOPUS database using the keyword "Hospital Health Services." The search identified 342,847 articles, which were then screened for relevance based on document type, language, publication area, and open access status, narrowing the pool to 76 articles. Following a detailed eligibility assessment, 17 articles were included in the final analysis. These articles covered various aspects of hospital operations, including leadership and management practices, health promotion initiatives, technological innovations, and patient satisfaction. Key findings highlight the critical role of adaptive and strategic leadership in enhancing hospital efficiency and patient care quality. Health promotion initiatives were found to be essential for improving population health, especially when integrated with technological advancements. The implementation of advanced health information technologies, such as electronic health records and digital alerts, significantly improved service efficiency and patient outcomes. Patient satisfaction, influenced by the quality of care, personalized interactions, and supportive environments for healthcare professionals, emerged as a fundamental component of effective healthcare delivery. The implications of this study suggest that hospital administrators and policymakers should prioritize adaptive leadership, integrate health promotion with technology, invest in advanced health information systems, and focus on enhancing patient satisfaction through improved care quality and supportive environments. These strategies are critical for achieving sustainable improvements in hospital health services and overall patient outcomes.